Very large data bases 2002 : proceedings of the Twenty-eighth International Conference on Very Large Data Bases, Hong Kong SAR, China, 20-23 August 2002 - Bernstein, Philip A. (Morgan Kaufmann, 2002)
Proceedings of the 28th Annual International Conference on Very Large Data Bases held in Hong Kong, China on August 20-23, 2002. Organized by the VLDB Endowment, VLDB is the premier international conference on database technology.